2003
DOI: 10.1213/01.ane.0000092917.96558.3c
|View full text |Cite
|
Sign up to set email alerts
|

The Sympathomimetic Actions of l-Ephedrine and d-Pseudoephedrine: Direct Receptor Activation or Norepinephrine Release?

Abstract: The indirectly sympathomimetic property of l-ephedrine may be one of the mechanisms to explain why ephedrine is preferred over alpha-adrenergic agonists as a vasopressor for treatment of intraspinal anesthesia-induced hypotension in obstetrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 16 publications
1
32
3
1
Order By: Relevance
“…Ephedrine has been shown to bind to ␤1, ␤2, and ␤3 receptors expressed on Chinese hamster ovary cells (Vansal and Feller, 1999). It has been reported that despite evidence that ephedrine has direct effects in isolated tissues, the pressor response was shown to be indirectly mediated in vivo in the rat (Kobayashi et al, 2003). In contrast, the present results demonstrate that responses to ephedrine are directly mediated, whereas responses to amphetamine are dependent on an indirect mechanism.…”
Section: Downloaded Fromcontrasting
confidence: 82%
See 1 more Smart Citation
“…Ephedrine has been shown to bind to ␤1, ␤2, and ␤3 receptors expressed on Chinese hamster ovary cells (Vansal and Feller, 1999). It has been reported that despite evidence that ephedrine has direct effects in isolated tissues, the pressor response was shown to be indirectly mediated in vivo in the rat (Kobayashi et al, 2003). In contrast, the present results demonstrate that responses to ephedrine are directly mediated, whereas responses to amphetamine are dependent on an indirect mechanism.…”
Section: Downloaded Fromcontrasting
confidence: 82%
“…Other studies in isolated tissues have shown that ephedrine acts by direct stimulation of adrenergic receptors (Tye et al, 1967;Waldeck and Widmark, 1985;Bao et al, 1990;Kawasuji et al, 1996). It has recently been reported that despite evidence that ephedrine has direct effects in isolated tissues, the pressor response is completely indirectly mediated in vivo in the rat (Kobayashi et al, 2003).…”
mentioning
confidence: 97%
“…Pressure ( have been inconsistent (Kobayashi et al, 2003;Liles et al, 2006). Therefore, the present experiments were carried out in mice with targeted disruption of the Dbh gene that cannot synthesize noradrenaline (Thomas et al, 1995(Thomas et al, , 1997(Thomas et al, , 1998).…”
Section: Change In Mean Arterialmentioning
confidence: 99%
“…However, the mechanism of the pressor response to ephedrine is uncertain. Ephedrine has been thought to elicit a pressor response through the release of noradrenaline from adrenergic terminals (Fleckenstein and Burn, 1953;Burn and Rand, 1958;DeMoraes and Carvalho, 1968;Kobayashi et al, 2003). It has been reported that the pressor response to ephedrine is reduced following treatment with 6-hydroxydopamine to destroy adrenergic nerve terminals (Kobayashi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the aerial parts of different Ephedra species contain active alkaloids (Yeung, 1980), including the phenylpropylamino alkaloids ephedrine and pseudoephedrine. Ephedrine is a sympathomimetic agent (Astrup et al, 1995;Kobayashi et al, 2003) and its consumption may lead to increased cardiac rate and contractility as well as overstimulation of the central nervous system (Abourashed et al, 2003;Krizevski et al, 2012). However, E. foeminea species specifically lacks both ephedrine and pseudoephedrine (Abourashed et al, 2003;Krizevski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%